Kit Carson - Beals, Frank L. (Frank Lee), 1881-1972 (American adventure series (Evanston, Ill.), 1960)
A biography of Kit Carson, a frontiersman from the age of 16 to his days with Fremont's Oregon Expedition and the Mexican Wars.